Developing Learning Service Models for Slow Learners to Optimize Inclusive Education in Semarang Junior High School - Fajriah, Fajriah; Samsudi, Samsudi; Haryono, Haryono (Universitas Negeri Semarang, 2021)
The preparation of adaptive learning models for children with special needs is important because nowadays there is no policy set out in providing appropriate education services based on their specific needs. The slow learner inclusivity type is currently could be accommodated in regular schools. Therefore, this study aims to develop a model of learning services for slow learners. Using research and development methods, we conducted qualitative analysis for model preparation and quantitative analysis to analyze its effectiveness. The curriculum adaptation service model used is substitution. The results of the trials showed that there was a significant average difference before and after the implementation. Providing learning services with this model can make children better at responding to conversations and working with others, able to do independent activities, and able to control concentration in learning. These results require more operational policy support so that they can be implemented more easily.